Studies on Hydroxyl Radical Formation and Correlated Photoflocculation Process Using Degraded Wood Leachate as a CDOM Source - Sun, Luni; Mopper, Kenneth (Frontiers in Marine Science, 2016)
The iron-poor leachate from decaying wood can be an important source of colored dissolved organic matter (CDOM) in natural waters. In this study, we examined hydroxyl radical (•OH) formation with respect to photoreactivity of wood leachate DOM, the Fenton reaction, and photoflocculation. The relationship of •OH photoproduction rate and leachate optical properties (UV-visible absorption and fluorescence excitation-emission matrices (EEMS) coupled with PARAFAC analysis) were studied during irradiation in a UV solar simulator. The results showed that the •OH photochemical formation rate is strongly related to humic-like fluorescence as characterized by EEMS-PARAFAC analyses, and these fluorescence components are more photolabile than most of the other CDOM components. Fourier transform infrared spectroscopy (FT-IR) indicates the photodegradation of lignin-related structures. To examine the role of iron, Fe speciation (particulate Fe, organically-complexed Fe(II), organically-complexed Fe(III), free Fe(II), and free Fe(III)) were measured in the leachate samples amended with Fe. The addition of Fe accelerated •OH production substantially, and Fe was rapidly photochemically cycled between Fe(II) and Fe(III). The photodegradation of iron complexing ligands appears to play an important role in DOM photoflocculation.